Sensitivity and response time of an ozone sensor - Ngajikin, Nor Hafizah (2013)
The use of optical retro-reflectors in improving the sensitivity and response time of an optical sensor based on optical absorption spectroscopy for the measurement of ozone gas is presented. Two optical retro-reflectors are employed in the design of a 30cm and 20 cm absorption gas cells. Our analysis shows that, in the 30cm gas cell, a sensitivity of 0.0451ppm and 0.0901ppm is achievable while in the 20cm gas cell we can achieve a sensitivity value of 0.0681ppm. However these sensitivity values are dependent on the optical density of the sensor. In general gas cell with wider diameters has potentials for a faster response time.